How to Conduct Research Projects in Translation Studies - Martín Cieri (Perspectivas Metodológicas​)
In recent years, the field of Translation Studies has experienced steady growth in both academic production and epistemological consolidation. This development has been accompanied by an increasing demand for rigorous training aimed at translators and interpreters who are not only engaged in professional practice, but also actively involved in the generation of knowledge through systematic research processes. Within this framework, the book under review emerges as a significant contribution, offering conceptual and methodological tools that guide research practice and strengthen the role of investigation within the disciplinary field of translation.